Assessment of a non-linear diffusive-convective model for the ISOVPE MCT growth - Moyano, Edgardo A. (2000)
Hg1-uCduTe (MCT) is the most important semiconductor for infrared detection. The ISOVPE technique allows good quality MCT epilayers . For technological and scientific reasons it is interesting to have a model which accurately describes this MCT growth technique. Hence, a non-linear diffusion-convection problem which describes ISOVPE MCT film growth was numerically solved by means of discrete mathematics. It has been found that the model describes a diffusion-limited process in accordance with the experimental evidence. As the theoretical and experimental composition profiles were remarkably different in accordance with other authors, it was supposed in the model that a finite rate in the surface reaction enabled a good fit. A numerical value of the surface reaction constant rate was obtained for the experimental conditions of this work which enabled us to determine that the deposition rate has a mixed control. It is expected that the control of the surface reaction rate becomes more important when a lower growth temperature is used.